3D Printed Tuneable Silicone Foams via Direct Templating Approach - Kenrick Weiting Tie,; Jia Huey Sim,; Purani Mohana Sundaram,; Jing Yuen Tey,; Wei Hong Yeo,; Zhi Hua Lee,; Law Yong Ng, (International Journal of Integrated Engineering, 2025)
Silicone is well-known for its appealing properties like high elasticity, hydrophobicity and biocompatibility, which translates to diverse applications including silicone foams. However, current foaming methods are complex, lengthy and involves hazardous chemicals. The direct templating approach tackles these complications by saturating the silicone precursors with sacrificial templates, e.g. salts or sugar crystals. These templates are leached out in appropriate solvents after vulcanization, leaving behind porous structures. The resulting pores and mechanical properties of the foams can be tuned by varying the quantity of sacrificial templates introduced. In addition, 3D printed architectures present greater degree of complexity for said silicone foams. Herein, facile silicone foams with tuneable properties are fabricated via Direct Ink Writing (DIW) with the inclusion of glucose sugar crystals into a one-part room temperature vulcanizing (RTV-1) silicone formulation, with deionized water as the eco-friendly solvent. The silicone ink formulations were proven to fulfil viscoelastic requirements of DIW. Pore morphologies of formulated foams with varied glucose content of 15 phr to 55 phr were characterized by SEM. The results showed presence of macropores with pore sizes ranging from 26.44 µm to 52.39 µm and porosity ranging from 15.03 % to 31.60 %. The pore size and porosity of the foam samples were found to be linearly proportional to the amount of glucose content. Tensile tests unveiled that with increasing sugar content, mechanical properties of said foams had been varied with tensile strength (0.96 – 0.59 MPa), elongation at break (511 - 362 %), and Young’s modulus (0.50 - 0.37 MPa). The foams also displayed decreasing Shore A hardness (35.8 – 30.1) as porosity increased. This simplistic approach represents a feasible method of creating silicone foams with tuneable properties using easily attainable and safe materials.